Upgrading and Increasing Value of Souvenir Products of Tourist Attractions; Experience the Charm of the Old City Life Style, Phra Nakhon Si Ayutthaya Province - Chaemchamrus, Kamtorn; Erb-im, Nanthannit; Phuanpoh, Yanisa; Sermchayut, Rudee (Arts of Management Journal, 2022)
The objectives of this article are 1) to study souvenirs of Phra Nakhon Si Ayutthaya historic city’s tourist attractions, 2) to study the souvenir shopping behavior of the tourists in the historic city’s tourist attractions and 3) to upgrade and increase the value of the souvenirs in the historic city’s tourist attractions. This is mixed methods research. The first phase was quantitative research using questionnaires and collecting data from a random sample of 400 people. Data analysis was performed using inferential statistics including T-test and F-test. The second phase was qualitative research using a semi-structured interview form, in-depth interview with five government agencies representatives and focus group discussion with people in Phu Khao Thong sub-district. The results were then used in focus group discussions with the five government agencies. Content analysis was used for the qualitative analysis of the data and the data source triangulation was used as proof of validity. The results showed that; 1) There are 4 categories of outstanding souvenir products: food, utensils and accessories, clothing and apparel, and herbs. 2) In terms of souvenir shopping behavior, tourists purchase products by considering product features, reflection of local identity and their artistic value and beauty respectively. 3) There is an upgrade and increase in the value of the souvenir, which is a carp. It is the identity of Phra Nakhon Si Ayutthaya. It is introduced into the conceptualization process with an emphasis on product features. There is a market study and product development along with the development of the S-F-U-P-C Model until it becomes 5 new products Including 1) a Thai-style fish mobile deodorizer 2) Thai-style fish mobiles for decoration 3) a Thai-style fish lamp 4) Thai fabric with carp pattern and 5) a Fabric bag painted with carp pattern.